2020
DOI: 10.1101/2020.08.17.20176560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repercussions of the Covid-19 Pandemic on the Mental Health of Pregnant and Puerperal Women: A Systematic Review

Abstract: Background: The Coronavirus Disease 2019 (COVID-19) pandemic has caused negative impacts on the physical and mental health of the population worldwide. Pregnant and puerperal women comprise the population most vulnerable to impacts on mental health. Objective: To synthesize the scientific evidence on the repercussions of the COVID-19 pandemic on the mental health of pregnant and puerperal women. Methods: systematic review focused on answering the question what is the impact of the COVID-19 pandemic on the men… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The heightened levels of anxiety and stress during the COVID-19 pandemic found among Baby Buddy users are consistent with research among the general UK population [17] and perinatal populations from other countries [18]. A study of over 4000 pregnant women in China reported a significantly higher rate of depressive symptoms (measured on the Edinburgh Postnatal Depression Scale), suggesting an increased risk of mental illness, including self-harm behaviors [19].…”
Section: Principal Findingssupporting
confidence: 74%
“…The heightened levels of anxiety and stress during the COVID-19 pandemic found among Baby Buddy users are consistent with research among the general UK population [17] and perinatal populations from other countries [18]. A study of over 4000 pregnant women in China reported a significantly higher rate of depressive symptoms (measured on the Edinburgh Postnatal Depression Scale), suggesting an increased risk of mental illness, including self-harm behaviors [19].…”
Section: Principal Findingssupporting
confidence: 74%
“…Several explanations may account for this result. For instance, it is possible that during this period, mothers were more worried and felt more fear of contracting COVID‐19, which may have led them to focus more on the future (Vieira et al., 2020 ) and be less mindful of the present moment. In addition, the need for social isolation during this pandemic phase and the consequent lack of instrumental support (e.g., assistance in domestic tasks and with infant care) may have left mothers feeling overwhelmed in their role as a mother and dealing with the baby's demands, reducing their ability to accept their mistakes and failures in parenting situations.…”
Section: Discussionmentioning
confidence: 99%
“… 33 A systematic review investigating the impact of the COVID-19 pandemic on the mental health of pregnant women revealed that social distancing, fear of infection, current economic situation, media pressure, disrupted routines, and the change in family rituals were intensifying factors of psychological distress among pregnant women. 34 The presence of PTSD symptoms among pregnant women was shown to have acute (e.g. preterm delivery) and long-term consequences (e.g.…”
Section: Discussionmentioning
confidence: 99%